Associations between childhood maltreatment and suicidal ideation in depressed adolescents: The mediating effect of alexithymia and insomnia. (January 2023) - Li, Xiaoyue; Wang, Xixin; Sun, Liang; Hu, Yu; Xia, Lei; Wang, Song; Guo, Chunyan; Shi, Yudong; Yuan, Xiaoping; Zhang, Kai; Liu, Huanzhong
Abstract: Background: People with depression appear to experience higher levels of childhood maltreatment (CM) and suicidal behaviour. However, no studies have discussed the factors through which CM influences suicidal ideation (SI) in adolescents with depression. The present study examined the effects of alexithymia and insomnia on the relationship between CM and SI in a population of Chinese adolescents with depression. Methods: A total of 262 adolescents with depression (198 females) completed the Childhood Trauma Questionnaire-Short Form, the Toronto Alexithymia Scale-20, the Insomnia Severity Index, and the Positive and Negative Suicide Ideation. Results: With the exception of sexual abuse (SA), four types of CM were associated with SI in depressed individuals. The highest incidence was found for physical neglect (PN) (65.27 %). Alexithymia and insomnia were both positively associated with SI. Externally oriented thinking (EOT) and insomnia had significant mediating effects on the relationship between emotional abuse (EA) and SI. EOT and insomnia also had significant mediating effects on the relationship between physical neglect (PN) and SI. Limitations: The major limitations of this study include the impacts of cross-sectional studies and recall bias on the results. Conclusions: Alexithymia and insomnia have an impact on SI in adolescents with depression who have experienced CM. Therefore, we should be aware of the impact of alexithymia and insomnia on depression patients. Rates of suicide among adolescents with depression should be reduced by identifying targeted measures. Highlights: Insomnia and alexithymia affect suicidal ideation in depressed adolescents. EOT and insomnia had a effect on the relationship between emotional abuse and suicidal ideation. EOT and insomnia as mediators of childhood physical neglect leading to suicidal ideation in depressed adolescents.